Are ICT Tools Recognized Enough as Management Support in Croatian Tourism? - Daniela Grabin Praničević; Judita Peterlin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The Information and Communication Technology (ICT) have been implemented in tourism as a supporting tool for different related activities. The main research question the authors set as: Have different Croatian tourism subjects recognized the relevance of the new technical solutions and integrated it in their business models to support the management activities and related leadership trends? In the theoretical part the concept of tourism management based on leadership trends and supported by ICT solutions is elaborated. In the empirical part general level of few tourism stakeholders' ICT usage is investigated. The research was conducted in spring 2016 and was based on 354 tourism stakeholder guests' perceptions. The contribution is practical as well as theoretical. An overview of the main actual ICT solutions available to tourism sector presents a practical implication of this research while developing framework appropriate for assessing the ICT as tourism management support stands as academic contribution.
Keywords: A22; I30; M10; M14; 330; ICT tools; leadership; management; tourism stakeholders; Croatia